SOME ISSUES OF EFFECTIVE USE OF MUSEUM ACTIVITIES IN THE DEVELOPMENT OF TOURISM (International Conference on Education, Psychology and Humanities, 2026)
In Uzbekistan, during the years of independence, especially in the recent period, the tourism sector has begun to be considered as one of the important strategic sectors of the national economy. The country's rich historical and cultural heritage, ancient cities, architectural monuments, and traditional culture allow us to raise the tourism potential to a high level. From this point of view, the activities of museums manifest themselves as an important socio-cultural institution in the development of tourism. Museums serve not only to preserve the material and spiritual heritage, but also to form a positive image of the country by presenting it to the general public, especially foreign and domestic tourists, on a scientific basis.
Keywords: public, especially foreign and domestic tourists, on a scientific basis.